Exposition et conservation de Tolstoï et les poules, une œuvre d’Oleg Kulik - Béatrice Guilloux (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Exhibition and preservation of Tolstoy and the chickens a work by Oleg KulikIn the collection of the Frac des Pays de la Loire are several works using animals or materials indissociable from animals, notably Tolstoï et les poules (Tolstoy and the chickens) by Oleg Kulik. This example enables us to look at the questions and strategies of the management of conservation and preservation specific to collections of contemporary art, especially those works which carry the risk of contaminating other works.